The impact of regional institutional quality on firm innovation: evidence from Africa - (:unkn) unknown (Taylor and Francis Ltd., 2021)
The main aim of this study is to empirically examine the role of regional institutional quality, and compare the relative importance of three different institutional arrangements, namely regulatory quality, rule of law, and corruption, on propensity of firm innovation in African countries. To this end, we used the most recent World Bank Enterprise Survey (WBES) of firms from 19 African countries. Our empirical investigation using multilevel logistic regression has drawn three important conclusions. First, there is no significant relationship between firm-specific factors, such as age, ownership, and exporting, and firm innovation. Nonetheless, firms’ propensity to innovate is significantly determined by the size of the firm, R&D expenditures, on-the-job training (OJT), and capability of managers/owners to adopt new technologies. Second, the innovation performance of firms is significantly affected by regional institutional quality. Third, among different regional institutional arrangements, reducing corruption and maintaining rule of law appeared to matter the most for firm innovation. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Africa; Innovation; multilevel logistic regression; regional institutions